2015
DOI: 10.1186/s12989-015-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nanosilver on various DNA lesions and HPRT gene mutations – effects of charge and surface coating

Abstract: BackgroundThe main goal of this research was to study the interactions of a fully characterized set of silver nanomaterials (Ag ENMs) with cells in vitro, according to the standards of Good Laboratory Practices (GLP), to assure the quality of nanotoxicology research. We were interested in whether Ag ENMs synthesized by the same method, with the same size distribution, shape and specific surface area, but with different charges and surface compositions could give different biological responses.MethodsA range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 59 publications
(87 reference statements)
2
40
0
Order By: Relevance
“…They caused a decrease in the number of cells (Ag_SDS) and, which is most striking, acidication and swelling of lysosomes (T6:RT-DL samples), which presumably precedes lysosomal membrane rupture. 31 Thus, Ag_SDS NPs' ability to induce cytotoxicity, measured as a decrease in the cell number (HCS, PE) increased with aging, regardless of the storage conditions, and may be caused by Ag dissolution resulting in increasing concentrations of free SDS. 5), suggests that the increased concentration of Ag + exerts the nal Ag_SDS (PE) and Ag_Citrate (HCS) toxicity, which is consistent with previous reports.…”
Section: Biological Effects Of "Fresh Vs Aged" Agnpsmentioning
confidence: 95%
See 1 more Smart Citation
“…They caused a decrease in the number of cells (Ag_SDS) and, which is most striking, acidication and swelling of lysosomes (T6:RT-DL samples), which presumably precedes lysosomal membrane rupture. 31 Thus, Ag_SDS NPs' ability to induce cytotoxicity, measured as a decrease in the cell number (HCS, PE) increased with aging, regardless of the storage conditions, and may be caused by Ag dissolution resulting in increasing concentrations of free SDS. 5), suggests that the increased concentration of Ag + exerts the nal Ag_SDS (PE) and Ag_Citrate (HCS) toxicity, which is consistent with previous reports.…”
Section: Biological Effects Of "Fresh Vs Aged" Agnpsmentioning
confidence: 95%
“…30,31 Six different stabilizers were utilized: two negatively charged: 3-sodium citrate (Na 3 C 6 H 5 O 7 ; Fisher Scientic, Schwerte, Germany) and sodium dodecyl sulfate (SDS; Sigma-Aldrich, St. Louis, MO, USA); two positively charged: chitosan (high molecular weight; Sigma-Aldrich, Tauirchen, Germany) and BYK-9076® (BYK-Chemie, Wesel, Germany); and two neutral: Tween 80® (Sigma-Aldrich, Tauirchen, Germany) and DISPERBYK-192® (BYK-Chemie, Wesel, Germany). Silver nitrate (AgNO 3 ; Heraeus, Hanau, Germany) was used as the metal precursor and sodium borohydride (NaBH 4 ; ACROS Organics, Geel, Belgium) as the reducing agent (modied protocol of Creighton et al).…”
Section: Nanoparticle Preparationmentioning
confidence: 99%
“…Mutations are assessed at a specific locus -often the HPRT (hypoxanthine phosphoribosyltransferase) or TK (thymidine kinase) genes (Wang et al, 2007;Huk et al, 2014Huk et al, , 2015Gabelova et al, 2017). These assays can detect a range of mutations, including deletions; however, the mouse lymphoma assay (based on the TK gene) detects deletions with higher efficiency compared with the HPRT gene mutation test (Johnson, 2012).…”
Section: Gene Mutationsmentioning
confidence: 99%
“…Assessing antitumor properties of NPs requires stability in investigation under in vitro cell culture conditions. The interactions between NPs and biomolecules present in the culture media, such as proteins and lipids, could change nanomaterial's characteristics [12]. For instance, research has demonstrated the formation of protein corona around NP surface due to interaction with cellular media, resulting in modifications of their physical properties and leading, for instance, to aggregation and sedimentation [13].…”
Section: Physicochemical Characteristics Of Nanomaterials and Their Imentioning
confidence: 99%
“…It is important to note that AgNPs_byk formed the smallest agglomerates in medium solution in comparison to other coated AgNPs, suggesting that size is an important factor in toxicity. To sum up, coated NPs display various biological in vitro effects depending mainly on their surface charge [12].…”
Section: Organically Coated Nanomaterialsmentioning
confidence: 99%